2017
DOI: 10.2495/cmem-v6-n1-176-185
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of flash-boiling through sharp-edged orifices

Abstract: Flash boiling is the rapid phase change of a pressurised fluid that emerges to ambient conditions below its vapour pressure. Flashing of a flowing liquid through an orifice or a nozzle can occur either inside or outside the nozzle depending on the local pressure and geometry. Vapour generation during flashing leads to interfacial interactions that eventually influence the jet.Empirical models in the literature for simulating the inter-phase heat transfer employ many simplifying assumptions, which limits their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Both the upstream and downstream velocities demonstrated a more uniform flow and larger jet core than the previous case. Similar parabolic shape behavior has been also observed in Lyras et al 14 and Lyras et al 31 Figure 9 compares the axial velocity u with CFD and ML-CFD. Compared to the standard CFD solution, the ML approach captures the flow within the nozzle relatively well, with more significant differences occurring downstream the nozzle, where the ML-CFD gives a smaller jet core.…”
Section: Varying (L D P) For P £ 10 Barsupporting
confidence: 84%
See 1 more Smart Citation
“…Both the upstream and downstream velocities demonstrated a more uniform flow and larger jet core than the previous case. Similar parabolic shape behavior has been also observed in Lyras et al 14 and Lyras et al 31 Figure 9 compares the axial velocity u with CFD and ML-CFD. Compared to the standard CFD solution, the ML approach captures the flow within the nozzle relatively well, with more significant differences occurring downstream the nozzle, where the ML-CFD gives a smaller jet core.…”
Section: Varying (L D P) For P £ 10 Barsupporting
confidence: 84%
“…( 4) have not been tested before for hydrogen jets. Nevertheless, previous works for superheated R134A and liquid nitrogen 10,30,31 have shown that these expressions can be deployed for other fuels. The changes of the mixture are taken into account in the momentum equation as follows.…”
Section: Numerical Modeling Of Flash Boilingmentioning
confidence: 99%
“…The value of Θ tends to decrease with increasing void fraction and non-dimensional pressure 21,23 . The HRM expressions have been used before for superheated R134A and liquid nitrogen 51,52 and are known to work for other superheated liquids as well such as iso-octane 53 and JP8 54 . The model has been shown to perform well without adjustment of constants either in the present work or in former efforts 23,53-55 .…”
Section: A Non-equilibrium Vapour Generationmentioning
confidence: 99%
“…This model considers the thermal non-equilibrium state of the flashing liquid by introducing a relaxation time and relating the evaporation rate to the deviation of the current mass fraction from an equilibrium value [3]. Finding a suitable description for the relaxation time is a challenging task, yet the model of Downar-Zapolski et al [12], which is an empirical fit to flashing water experiments, has shown a general applicability to several fluids and injection conditions [18,26,29,30]. Nevertheless, the model coefficients may require case specific adaptations which cannot be directly determined a priori and thus, model verification is required for each case [20,33].…”
Section: Introductionmentioning
confidence: 99%